Introducing communication theory : - West, Richard L. (Mc Graw Hill, 2004)
This text introduces the field of communication to students who may have little or no background in communication theory. The three overriding goals of the book are to help students understand the pervasiveness of theory in their lives, to demystify the theoretical process, and to help students become more systematic and critical in their thinking about theory. Chapter by chapter approach allows students to understand one theory at a time, staying focused on one theory before learning another theory